Improved migration of tumor ascites lymphocytes to ovarian cancer microenvironment by CXCR2 transduction. (3rd April 2018) - Idorn, Manja; Olsen, Maria; Halldórsdóttir, Hólmfrídur Rósa; Skadborg, Signe Koggersbøl; Pedersen, Magnus; Høgdall, Claus; Høgdall, Estrid; Met, Özcan; thor Straten, Per
ABSTRACT: Chemokines are essential mediators of cellular trafficking, interactions and tumor development. Though adoptive cell therapy (ACT) has been a tremendous success in the treatment of metastatic melanoma (MM), a major obstacle for successful ACT, is limited homing of effector T cells to immune suppressive tumor sites. We hypothesized that equipping T cells with chemokine receptors matching the chemokines of the tumor microenvironment, could improve tumor homing of T cells. T cells from malignant ascites (n = 13); blood from ovarian cancer (OC) patients (n = 14); and healthy donors (n = 13) were analyzed by flow cytometry. We found that FoxP3 + regulatory T cells accumulation in patients with OC associates with CCR4 expression. We characterized a chemokine profile of ascites chemokines, and expression of corresponding receptors on circulating T cells and tumor ascites lymphocytes (TALs). CCL22, CXCL9, CXCL10 and CXCL12 associated with enrichment of CCR4 +, CCR5 +, CXCR3 + and CXCR4 + T cells in ascites. Circulating T cells and TALs however did not express CXCR2, identifying CXCR2 as candidate for chemokine receptor transduction. TALs readily expressed IFNγ and TNFα upon stimulation despite the frequency decreasing with in vitro expansion. Lentiviral transduction of TALs (n = 4) with chemokine receptor CXCR2 significantly increased transwell migration of TALs towards rhIL8 and autologous ascites. The majority of expanded and transduced TALs were of a T effector memory subtype. This proof of concept study shows that chemokine receptor engineering with CXCR2 is feasible and improves homing of transduced TALs towards the OC microenvironment.